NATURAL LANGUAGE PROCESSING AND ITS APPLICATIONS IN BIOMETRICS VS. BLOCKCHAIN - P V, Rejina (ShodhKosh: Journal of Visual and Performing Arts, 2021)
Natural Language Processing (NLP) which is part of artificial intelligence, allows machines to work with human language. As more advanced technology is being developed, NLP sees wider use, primarily with biometrics and blockchain. With biometrics, we use physical features to verify a persons identity and blockchain provides safe and distributed data handling. In this paper, we review how NLP connects to these domains, note their main advantages and disadvantages and look at how it helps secure data and automates tasks. Statistics and hypothesis testing are applied to examine how effective NLP is in these markets.